2012
DOI: 10.1063/1.3700343
|View full text |Cite
|
Sign up to set email alerts
|

Spectral engineering of LaF3:Ce3+ nanoparticles: The role of Ce3+ in surface sites

Abstract: Due to the high surface-to-volume ratio, luminescence centers on the surface have relative dominance in the overall spectral response of nanoparticles. The luminescence of LaF3:Ce3+ nanoparticles was investigated in the spectral and temporal domains with a particular focus on the role of Ce3+ on the surface. These nanoparticles present two luminescence bands at 4.10eV and 4.37 eV attributed to Ce3+ transitions from the 5d level to the spin-orbit split 4f ground levels F-2(5/2) and F-2(7/2), in addition to a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…The decay curve for singly doped LaF:Ce 1 mol% was processed in the same way as for the co-doped samples, but with only a single-exponential function, and the lifetime was found to be 29 ns for the 287 nm emission and 31 ns for the 301 nm emission. These values are similar to the lifetime reported for smaller Ce-doped LaF 3 nanoparticles coated with undoped LaF 3 shells [18]. The decay time was slightly longer for the longer wavelength emission, as has been reported for Ce doped NaCaPO 4 [19].…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…The decay curve for singly doped LaF:Ce 1 mol% was processed in the same way as for the co-doped samples, but with only a single-exponential function, and the lifetime was found to be 29 ns for the 287 nm emission and 31 ns for the 301 nm emission. These values are similar to the lifetime reported for smaller Ce-doped LaF 3 nanoparticles coated with undoped LaF 3 shells [18]. The decay time was slightly longer for the longer wavelength emission, as has been reported for Ce doped NaCaPO 4 [19].…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…The porous structures will generate some surface defects, which cause luminescence quenching effect. Recently, some reports indicated that the luminescence properties of LaF 3 :Ce 3+ nanoparticles are related to the energy transfer through multipolar interaction between Ce 3+ in the core and quenching defects on the surface . Similarly, we suppose that the surface effect of nanofibers, as well as the anisotropy and space dimensionality, will lead to the most Tb 3+ ions residing on the surface, and the energy transfer between adjacent Tb 3+ ions on the surface is intensified, which can block luminescence quenching effect.…”
Section: Resultsmentioning
confidence: 85%
“…As the Tb 3þ doping concentration increases from 1 to 5%, the excitation and emission intensities of nanofibers increase gradually. It can be observed from where I 0 is the initial emission intensity at t ¼ 0, and t is the in the core and quenching defects on the surface [29]. Similarly, we suppose that the surface effect of nanofibers, as well as the anisotropy and space dimensionality, will lead to the most Tb 3þ ions residing on the surface, and the energy transfer between adjacent Tb 3þ ions on the surface is intensified, which can block luminescence quenching effect.…”
Section: Photoluminescence Properties Of Lubomentioning
confidence: 90%
“…In fact, Ce 3+ ions are usually exploited for their very large absorption and emission features in the UV and visible regions but they also have a strong interaction with the crystalline lattice and this leads to large energy losses inside the material. Moreover, the exact location of these bands is strongly host-dependent and their properties are well-studied both in bulk and nanocrystalline hosts [115]. In nano fiber morphology, Ce 3+ optical properties have been studied either as single dopant in TiO 2 [67], YAG [77,78] and ZnO [21] or in conjunction with Tb 3+ in LaPO 4 [52], YAG [74] and Y 2 SiO 5 [85].…”
Section: Electrospun Rare Earth Doped Crystal Fibers 41 Electrospun Fibers With Stokes Emissionsmentioning
confidence: 99%